Toward the feldspar alternative for cosmogenic 10Be applications in mafic environment - Zerathe, Swann (2021)
In situ-produced 10Be is one of the most commonly used TCN in quantitative geomorphology due to the fact that its production rate is relatively well constrained in the ubiquitous quartz mineral whose integrity minimizes the possibility of contamination by meteoric 10Be. Easily decontaminated from meteoric 10Be, it is in addition reliably measured using the Accelerator Mass Spectrometry technique for which its detection limit is lower than 104 at.g-1. However, volcanic or mafic areas are generally quartz free, which hamper the routine use of 10Be. In the case of a quartz poor lithology, an alternative possibility is to rely on 10Be - feldspars. Two preliminary studies (Kober et al., 2005 and Blard et al., 2013a) already provided promising results, demonstrating that (1) the decontamination protocol classically applied to quartz (Brown et al., 1991) efficiently removes all the meteoric 10Be contamination from the feldspar grains and (2) the total production rate of 10Be in feldspar is 8 to 10 % lower than that in quartz. However, only two samples were analyzed in both studies. In order to better constrain the 10Be in situ-production rate within feldspars, the number of samples analyzed needs to be increased. In this study, we developed a new chemical protocol for the 10Be extraction from feldspar matrices, and to cross-calibrate the total 10Be in situ-production rate in feldspar (P10fsp) against the total 3He production rate in pyroxene (P3px). The cosmogenic 3He and 10Be concentrations were measured, respectively, in pyroxene and feldspar extracted from eight samples of ignimbrite boulders from a giant landslide located between 800 and 2500 m in the high central Andes of Southern Peru. This area is ideally located, since two studies have already determined the local total 3He production rate in pyroxene on the nearby Altiplano (Blard et al., 2013b; Delunel et al., 2016).